Dynamic Analysis of DNA Damage by Flow Cytometry and FISH - Demetrios P. Matthopoulos (The Scientific World Journal)
The micronucleus assay, developed to assess DNA damage induced by noxious agents, supplies information on whether the damage is due to clastogenic or aneugenic action. Although it is the test that can be used to assess agents' toxicity, it cannot provide information on the molecular events that result in the induction of micronuclei. To study the molecular events, the combination of both microscopic and analytical techniques is required. Flow-sorting induced micronuclei, based on their DNA content, in combination with chromosomal FISH and other molecular techniques, may provide information on these events.